Benzodiazepine prescrbing in the Republic of Srpska: analysis of prescribing patterns in primary health care - Maksimović, Žana M; Stajić, Mladen; Lončar-Stojiljković, Dragana (Scripta Medica, 2019)
Introduction. Benzodiazepines (BZDs) are very often (in)appropriately prescribed drugs. The aim of this study is to analyse physicians' prescribing patterns for BZD in the Republic of Srpska, and to assess to what extent primary diagnosis determine the dose and the length of use of BZDs. Methods. A retrospective analysis of the physicians' prescription habits based on the database of Family Medicine Information Systems of the Republic of Srpska, as well as on data from patient’s medical record were performed. Patients’ socio-demographic and clinical characteristics, including the data on the type and dose of BZDs prescribed, were recorded and evaluated. Results. BZDs were mostly prescribed for anxiety disorders (30.05%), for depressive disorders (17.54%), and for anxiety-depressive disorders (10.86%). A significant amount of BZDs was prescribed for non-psychiatric diagnoses (23.81%). Patients suffering from psychotic disorders were taking the highest dose of BZD and for the longest periods of time (p